Pengaruh Citra Merek, Kualitas Produk, dan Harga terhadap Keputusan Pembelian Smartphone Samsung pada Mahasiswa Institut Teknologi Indonesia - Afina Putri Vindiana; Fauziah Lestari (Jurakunman (Jurnal Akuntansi dan Manajemen), 2023)
The aim of this study is to determine the effect of brand image, product quality, and price on purchasing decision on Samsung smartphone within the students of Institut Teknologi Indonesia. 163 respondents were collected using purposive sampling, which means that each respondent has to be a user of a Samsung smartphone. This study used Structural Equation Modelling (SEM) with Partial Least Square (PLS) approach on SmartPLS3 Software as an analysis method. The results of this study showed: 1). Brand image has significant effect on purchasing decision with an original value of 0.165 and P-value of 0.071. 2). Product quality has significant effect on purchasing decision with an original value of 0.454 and P-value of 0.000. 3). Price has significant effect on purchasing decision with an original value of 0.358 and P-value of 0.000. 4). The result of Goodness of Fit (GoF) in this study showed that the model is strongly fit and matched its variables with a value of 0.455.